2013
DOI: 10.1111/ced.12189
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the sweat-derived innate defence antimicrobial peptide dermcidin is not impaired inStaphylococcus aureuscolonization or recurrent skin infections

Abstract: Antimicrobial peptides are an integral part of innate immunity, and contribute to the protection of human skin from Staphylococcus aureus colonization and infection. We sought to investigate whether the expression of the eccrine sweat-derived staphylocidal antimicrobial peptide dermcidin might influence S. aureus colonization or recurrent skin and soft-tissue infections (SSTIs). Eccrine sweat was collected from 18 patients with recurrent S. aureus SSTIs, 28 patients who were intermittent or permanent S. aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Bacterial and viral infections are a major threat to human health; these invading pathogens have evolved resistance to available small-molecule antimicrobial therapeutics (Davies and Davies, 2010). Skin is the organ most exposed between the body and microorganisms, including common antibiotic resistant bacteria such as Staphylococcus aureus (Rieg et al, 2014). Schittek et al (2001) found that dermcidin has antimicrobial activity against Escherichia coli, Enterococcus faecalis, Staphylococcus aureus, and Candida albicans, which limits skin infection of potential pathogens a few hours after bacterial colonization, but that lactoferrin in sweat does not show an effective role in the defense against bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial and viral infections are a major threat to human health; these invading pathogens have evolved resistance to available small-molecule antimicrobial therapeutics (Davies and Davies, 2010). Skin is the organ most exposed between the body and microorganisms, including common antibiotic resistant bacteria such as Staphylococcus aureus (Rieg et al, 2014). Schittek et al (2001) found that dermcidin has antimicrobial activity against Escherichia coli, Enterococcus faecalis, Staphylococcus aureus, and Candida albicans, which limits skin infection of potential pathogens a few hours after bacterial colonization, but that lactoferrin in sweat does not show an effective role in the defense against bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dermcidin variants as well as fragments were also detected. It appears that the level of dermcidin did not vary between healthy people and infected patients [ 91 ]. In addition, dermcidin may be related to other human diseases such as cancer and atherosclerosis [ 92 , 93 ].…”
Section: Identification Of Human Antimicrobial Peptidesmentioning
confidence: 99%
“…This lack of antimicrobial defense correlated with an impaired ability of sweat to eradicate bacteria on the skin of these patients (Rieg et al, 2005;Schittek, 2011). In contrast, Rieg and colleagues recently reported in a correlation study that patients with recurrent S. aureus skin and soft tissue infections and healthy people have a comparable level of dermcidin-derived peptides in their sweat (Rieg et al, 2014). The high abundance of dermcidin in the secretome of healthy individuals, which is known to be exclusively expressed by eccrine sweat glands in the skin (Rieg et al, 2004;Schittek, 2012), suggests that a majority of the identified proteins in the skin secretome of healthy individuals are derived from eccrine sweat.…”
Section: Prolactin-inducible Protein (P12273)mentioning
confidence: 98%